2018
DOI: 10.1109/tuffc.2018.2793195
|View full text |Cite
|
Sign up to set email alerts
|

Strategies to Obtain Subpitch Precision in Lateral Motion Estimation in Ultrasound Elastography

Abstract: In elastography, conventional linear array (CLA)-based RF data acquisition provides more accurate displacement measurements in the direction of beam propagation (axial direction) when compared to the perpendicular direction (lateral). Obtaining good quality lateral displacement estimates in ultrasound (US) elastography will lead to several benefits such as obtaining accurate inverse solutions, improving shear strain elastogram quality, getting good quality poroelastograms, and obtaining reliable rotation elast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Recently, we demonstrated a method that involved translating the focused US beam of CLA transducer in subpitch range by the following two approaches: (a) ABT (actuator beam translation) uses actuator-assisted beam translation and (b) EBT (electronic beam translation) electronically translates the subaperture by activating an odd and even number of consecutive elements sequentially. [24][25][26] These techniques were shown to provide an opportunity to improve the LDE quality in a relatively inexpensive manner. EBT approach, which requires only reprogramming of the beamforming sequence and no hardware modifications, can provide subaperture translation by only half the element size.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we demonstrated a method that involved translating the focused US beam of CLA transducer in subpitch range by the following two approaches: (a) ABT (actuator beam translation) uses actuator-assisted beam translation and (b) EBT (electronic beam translation) electronically translates the subaperture by activating an odd and even number of consecutive elements sequentially. [24][25][26] These techniques were shown to provide an opportunity to improve the LDE quality in a relatively inexpensive manner. EBT approach, which requires only reprogramming of the beamforming sequence and no hardware modifications, can provide subaperture translation by only half the element size.…”
Section: Introductionmentioning
confidence: 99%
“…50 Recently, there have been many methods proposed to obtain better quality lateral displacement estimates in elastography. 18,[51][52][53] We are currently investigating on combining the reference layer methodology and inverse reconstruction approach having access to better quality lateral displacement estimates, and compare it with the simple approach proposed here.…”
Section: Discussionmentioning
confidence: 99%
“…Another way of improving the RE image quality is by increasing the number of A-lines. In fact, some studies have shown that new A-lines can be incorporated by a sub-pitch translation of the ultrasonic beam or the ultrasound (US) probe itself [12], [13].…”
Section: Introductionmentioning
confidence: 99%